Systemic Factors During Metabolic Disease Progression Contribute to the Functional Decline of Adipose Tissue-Derived Mesenchymal Stem Cells in Reproductive Aged Females - Seboko, Ascentia M.; Conradie, M. M.; Kruger, M. J.; Ferris, William Frank; Conradie, Magda; van de Vyver, Mari (Frontiers in Physiology, 2018)
It is known that advanced metabolic disorders such as type 2 diabetes compromise the functional and regenerative capacity of endogenous adipose-tissue resident stem cells (ADSCs). It is however still unclear at which stage of disease progression ADSCs become compromised and whether systemic factors contribute to their functional decline. It was therefore hypothesized that inflammatory changes in the systemic microenvironment during distinct stages of disease progression negatively affect the functional capacity of ADSCs. A total of forty-seven (n=47) black African reproductive aged females (32 ± 8 years) (mean ± SD) were included in this study and subdivided into a) healthy lean (C)(body mass index, BMI ≤ 25 kg/m2), b) healthy overweight/obese (OB)(BMI ≥ 25 kg/m2), c) obese metabolic syndrome (MetS)(BMI ≥ 30 kg/m2) and d) type 2 diabetes mellitus (T2DM)(previously diagnosed and on treatment) groups. Participants underwent anthropometric assessments and a DXA scan to determine their body composition and adipose indices. Each persons’ systemic metabolic- (cholesterol, HDL, LDL, triglycerides, blood glucose) and inflammatory profiles (CRP, SDF1α, TNFα, IL6, IL8, IL10, IFNy) were also evaluated. Participant-derived serum was then used to treat an ADSC cell line in vitro and its effect on viability (MTT-based assay), proliferation (BrdU), migration (wound healing assay) and osteogenic differentiation assessed. When exposed to serum derived from overweight/obese individuals (with or without metabolic syndrome), both the proliferative and migratory responses of ADSCs were less pronounced than when exposed to healthy control serum. Serum IL6 concentrations were identified as a factor influencing the proliferation of ADSCs, suggesting that long-term disruption to the systemic cytokine balance can potentially disrupt the proliferative responses of ADSCs. Obese participant-derived serum (with and without metabolic syndrome) furthermore resulted in lipid accumulation during osteogenic differentiation. This study, therefore demonstrated that systemic factors in obese individuals, regardless of the presence of metabolic syndrome, can be detrimental to the multifunctional properties of ADSCs.